Health and Wellbeing: Sustainable Development Goals in Central America (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This scientific article addresses the efforts made by the Governments of the Central American Region on Health and Welfare issues promoted by the United Nations to give way out and continuity to the agenda of the Sustainable Development Goals (SDGs) of developing countries. From this approach, we will examine the strategies and operational plans that counteract the COVID-19 pandemic from the public Health systems of the Central American countries, thus contributing to the social, economic, political and cultural development of the Central American Region. Quality and public health is a right that every human being must possess, without any exclusion as established by the United Nations Human Rights. Health is the factor that most influences the advancement and progress of people and societies since without health there is no life. Health, in addition to ensuring a better quality of the environment, is also part of the daily processes of our life, that is why health is guaranteed in most countries of the world and access to it has been considered an essential human right. The Sustainable Development Goals (SDGs) highlight the importance of guaranteeing and promoting adequate health, protecting the well-being of the entire population. To meet and respond to needs, it is necessary to promote initiatives that eradicate certain diseases, finance health systems, improve sanitation and increase access to medical services. That is why Central American governments are making efforts to comply with the SDGs in the context of COVID-19 and thus guarantee the well-being of families.
Keywords: Systems of health; Sustainable development; Central America; COVID-19; Human Right